1978
DOI: 10.1002/art.1780210810
|View full text |Cite
|
Sign up to set email alerts
|

Complement‐fixing hidden rheumatoid factor in juvenile rheumatoid arthritis

Abstract: Fifteen to twenty percent of patients with juvenile rheumatoid arthritis (JRA) have positive latex fixation tests (LFT), whereas approximately 46% have previously been demonstrated to have hidden rheumatoid factors (RF), i.e., 19s IgM RF which can be detected by the LFT after acid separation of the IgM-containing fraction from serum. In this study, hidden RF were found in 59% of patients with seronegative JRA by use of a complementdependent hemolytic assay. The median titer of JRA patients was l :42, and in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

1978
1978
1989
1989

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…(7)(8)(9). Previous studies had demonstrated the association of active disease in JRA patients with polyarticular and pauciarticular onset who had 19S IgM RF or hidden 19S IgM RF circulating in their sera (5,6). The new findings of the 19S IgM RF association with IC formation in JRA initiated the present study.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…(7)(8)(9). Previous studies had demonstrated the association of active disease in JRA patients with polyarticular and pauciarticular onset who had 19S IgM RF or hidden 19S IgM RF circulating in their sera (5,6). The new findings of the 19S IgM RF association with IC formation in JRA initiated the present study.…”
mentioning
confidence: 71%
“…The presence of elevated IC as detected by the C1q binding assay or the Clq solid-phase assay, also, correlated with the presence of 19S IgM RF (2,3) and hidden 19S IgM RF (3) [i.e. 19S IgM RF which can be detected in the IgM-containing fraction by the hemolytic assay after separation of serum by acidgel filtration (5,6)]. IC presence has also correlated with active disease, demonstrating a connection with a more advanced stage of disease and possible prognostic parameter (3,4).…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…IgG-RF seems to play no significant role: it neither augmented nor diminished complement activation by IgM-RF. In contrast, considerable inhibition of complement activation by RF has been described using the hemolytic assay (8, 25).…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that hidden R F might be present in these patients was entertained because of recent studies in our laboratory that revealed the presence of hidden R F in high titer when a hemolytic assay was performed on separated IgM fractions of patients with seronegative JRA (21). Hidden R F is 19s IgM R F that probably has been complexed in the peripheral blood with 7s IgG and therefore is not detected by standard laboratory tests.…”
mentioning
confidence: 99%